Effect of the stress state on ultimate strain energy density in the failure of reinforced epoxy resin (Fracture and Structural Integrity, 2025)
Epoxy resin reinforced with 10% of TiO2 and pure epoxy resin are taken to exemplify the possibility of constructing a fracture locus for engineering organic polymers as a dependence of ultimate strain energy density in cohesive failure on the stress triaxiality factor in the range  and the Lode–Nadai coefficient . The fracture loci are based on the results of compressive testing of cylindrical specimens, tensile and compressive testing of bell-shaped specimens, dishing of thick-walled cup-shaped specimens, shearing of oblique dog-bone-shaped specimens. The tests were performed at 25 and −50 °C. The obtained dependences are approximated by interpolation formulas, and they can be used to predict the failure of structural components made of organic polymer materials mechanically affected under conditions of a complex stress state.
Keywords: Epoxy Resin; Stress triaxiality factor; Lode-Nadai coefficient; Strain energy density